Interictal widespread pressure hyperalgesia and aura: associations with vestibular migraine in a cross-sectional study - Toriyama, Toshihide; Hanaoka, Yoshiki; Horiuchi, Tetsuyoshi (Frontiers in Neurology, 2024)
Background Patients with vestibular migraine (VM) exhibit higher levels of central sensitization and share similar disorder characteristics with migraine with vestibular symptoms (MwVS), except in terms of disability. These patients experience fluctuating mechanical pain thresholds and persistent vestibular symptoms even without a migraine attack. Objective This study aimed to investigate whether interictal allodynia or hyperalgesia can differentiate between VM, MwVS, and migraine only. Methods We conducted a cross-sectional study of patients with episodic migraine aged between 18 and 65 years, categorized into three groups. A questionnaire was used to collect and compare demographic and clinical variables. Interictal widespread pressure hyperalgesia (IWPH) was evaluated using the Manual Tender Point Survey. Patients with tender point counts ≥7 were classified as having IWPH. Results The study included 163 patients: 31 with VM, 54 with MwVS, and 78 with migraine without vestibular symptoms (migraine only). We found that aura (p = 0.042, odds ratio 3.50, 95% confidence interval 1.26–10.4), tender point count (p < 0.001, d = 0.889, median difference = 2), and IWPH (p = 0.002, odds ratio 5.3, 95% confidence interval 1.80–17.2) were significantly associated with VM compared to MwVS. Aura and IWPH were significantly associated with VM. However, there were no significant associations observed for interictal allodynia or hyperalgesia between the other two groups. Conclusion IWPH and aura are associated with VM, indicating their potential roles in its pathogenesis. These findings may contribute to the differential diagnosis and management of migraine, potentially leading to targeted treatment strategies.